Pengaruh Work Life-Balance, Perceived Organizational Support (POS), dan Organizational Commitment Terhadap Retensi Karyawan pada Bank BTN Kantor Cabang Solo - Siwi, Maya Raka; Ahsani, Riska Fii (Teewan Journal Solutions, 2025)
Employee retention is a strategic effort made by companies to retain employees and encourage their commitment to the company within the expected period of time. Factors that influence employee retention include work-life balance, which is defined as an individual's ability to manage and balance work demands with personal and family responsibilities. Perceived organisational support (POS) refers to employees' belief that the organisation values their contributions and cares about their well-being. Organisational commitment is defined as an individual's strong desire to remain part of the organisation. This study aims to explore the significant influence of work-life balance, perceived organizational support (POS), and organisational commitment on employee retention at Bank BTN, Solo Branch Office. This research uses quantitative data, with the main data source being primary data. The population studied was all employees of Bank BTN, Solo Branch Office, and the sampling technique used was saturated sample with a total of 115 respondents. Data collection was carried out through distributing questionnaires online using Google Form. Data analysis was carried out with multiple linear regression using SPSS as a data processing tool. The results showed that work-life balance did not have a significant influence on employee retention at Bank BTN Solo Branch Office, while perceived organizational support (POS) and organisational commitment showed a significant influence. The R² value of 52% indicates that employee retention can be explained by work-life balance, perceived organizational support (POS), and organisational commitment variables.